Functionalised zinc oxide nanotube arrays as electrochemical sensors for the selective determination of glucose - Syed Muhammad Usman, Ali; Mohammad, Kasfhi; Zafar Hussain, Ibupoto; Muhammad, Fakhar-e-Alam; Uda, Hashim, Prof. Dr.; Magnus, Willander (The Institution of Engineering and Technology, 2012)
Link to publisher's homepage at http://www.theiet.org/